DysPReX: A Game-based Reading Tool for Children with Dyslexia - Jun, Cheang Jia; Abu Bakar, Nur Azzah; ChePa, Noraziah (Multidisciplinary Applied Research and Innovation, 2023)
Teaching the students with Dyslexia is very challenging as they naturally have difficulties in phonetic decoding. Past studies revealed that in the phonic-based intervention methods, students only made slow reading progress or no progress at all. A game called DysPReX was developed as an alternative intervention tool with little emphasis on phonics. The aim is to help the dyslexics to learn spelling and reading in a more fun and exciting way at their own pace. DysPReX was developed using Unity and runs on mobile devices and tablets which gives flexibility to the dyslexics to play it anywhere and anytime. The development took 4 months to complete and followed the standard development methodology which include planning, requirement gathering, design, prototyping and evaluation phases. DysPReX has several advantages over the existing dyslexic games: (1) it uses Bahasa Melayu as medium while majority of the existing off-the-shelf dyslexic games use English. To date, the number of dyslexic games in Bahasa Melayu is very limited; (2) it was developed according to the guideline for the dyslexic games, thus it incorporates the specific learning needs of the dyslexics. This includes what font type and size to use, the colors and the focus on the often-mixed-up letters such as b/d, u/n, m/w, g/q, p/q and b/p. DysPReX has been evaluated by 30 respondents and the results show positive feedback from the majority on the user interface, functionality, learnability, and satisfaction aspect with the score above 4.0. Therefore, the game fulfilled the respondents’ needs. DysPReX could contribute to the achievement of the United Nations sustainable development goals for quality education, reducing inequalities and sustainable communities. Quality education for the dyslexics can be achieved if they can overcome the hurdles in reading, which will allow the other goals to be achieved.